Pengaruh Picture Word Inductive Model berbantuan Classpoint dan Wordwall terhadap Kemampuan Membaca Pemahaman ditinjau dari Minat Baca Siswa - Anggi Apriliana; Tatat Hartati; Dadang Sunendar (Elementary Teacher Education Program, Majalengka University, 2024)
Abstract The background of this research is that students' literacy skills are still low, especially students' reading comprehension competence and reading interest which is quite worrying. The aim of this research is to obtain a comprehensive picture of the influence of the Picture Word Inductive Model (PWIM) assisted by classpoint and wordwall on reading comprehension abilities in terms of students' reading interest. The sample in this research was class II students at SDN Santaka, Cimanggung District, Sumedang Regency. The method used is an experiment with a 2 x 2 factorial design. The research results are as follows: 1) Learning to read comprehension using the PWIM model assisted by classpoint and wordwall is included in the quite effective category. 2) Based on the Two Ways Anova test, a sig value of 0.045 ˂ 0.05 is obtained, which can be concluded that there is a difference in the increase in reading comprehension ability between students with the PWIM model assisted by classpoint and wordwall. 3) Based on the Test of Between Subject Effect, a sig value of 0.424 ˃ 0.05 is obtained, it means that no significant difference between students' reading comprehension abilities in terms of reading interest. Students' reading interest has no effect on their reading comprehension ability. Students who have low reading interest do not necessarily have low reading comprehension abilities, nor do students who have high reading interest necessarily have high reading comprehension abilities. 4) Based on the calculation of the interaction effect, a sig value of 0.026 ˂ 0.05 is obtained, it means that there is an interaction effect between the reading model and reading interest on increasing students' reading comprehension abilities. Based on the results obtained, it can be concluded that learning using the PWIM model assisted by classpoint and wordwall media is quite effective in being implemented for students who have different reading interests (low reading interest and high reading interest). Keywords: Reading Comprehension; Students' Reading Interest; Picture Word Inductive Model; Classpoint; Wordwall Abstrak Latar belakang penelitian ini yaitu kemampuan literasi siswa masih rendah, terutama pada kompetensi membaca pemahaman dan minat baca siswa yang cukup memprihatinkan. Tujuan penelitian ini untuk memperoleh gambaran secara komprehensif mengenai pengaruh Picture Word Inductive Model (PWIM) berbantuan classpoint dan wordwall terhadap kemampuan membaca pemahaman ditinjau dari minat baca siswa. Sampel dalam penelitian ini adalah siswa kelas II SDN Santaka Kecamatan Cimanggung Kabupaten Sumedang. Metode yang digunakan adalah eksperimen dengan desain faktorial 2 x 2. Hasil penelitian sebagai berikut: 1) Pembelajaran membaca pemahaman dengan model PWIM berbantuan classpoint dan wordwall termasuk ke dalam kategori cukup efektif. 2) Berdasarkan pengujian Two Ways Anova diperoleh nilai sig sebesar 0,045 ˂ 0,05 artinya terdapat perbedaan peningkatan kemampuan membaca pemahaman antara siswa dengan model PWIM berbantuan classpoint dan wordwall. 3) Berdasarkan Test of Between Subject Effect diproleh nilai sig sebesar 0,424 ˃ 0,05 artinya tidak ada perbedaan yang signifikan antara kemampuan membaca pemahaman siswa ditinjau dari minat baca. Minat baca siswa tidak berpengaruh terhadap kemampuan membaca pemahaman. Siswa yang memiliki minat baca rendah belum tentu memiliki kemampuan membaca pemahaman rendah begitupun siswa yang memiliki minat baca tinggi belum tentu memiliki kemampuan membaca pemahaman tinggi. 4) Berdasarkan penghitungan efek interaksi diperoleh nilai sig sebesar 0,026 ˂ 0,05, artinya terdapat efek interaksi antara model membaca dengan minat baca terhadap peningkatan kemampuan membaca pemahaman siswa. Berdasarkan hasil yang diperoleh dapat disimpulkan bahwa pembelajaran dengan menerapkan model PWIM berbantuan media classpoint dan wordwall cukup efektif diimplementasikan pada siswa yang memiliki minat baca yang berbeda (minat baca rendah dan minat baca tinggi). Kata Kunci: Membaca Pemahaman; Minat Baca; Picture Word Inductive Model; Classpoint; Wordwall